Most Common Causes of Death Among Travelers on Aircraft and Maritime Vessels and During Land-Border Crossings Reported to the Centers for Disease Control and Prevention, 2008-2022 - Preston, Leigh Ellyn; King, Justice; Ortiz, Nancy; Alvarado-Ramy, Francisco; Brown, Clive; Mase, Sundari; Gearhart, Shannon L; Christensen, Deborah L; Pourakis, George A; Fonseca-Ford, Maureen; Rothney, Erin E; Sunavala, Zenia K; et al. (Public health reports (1974), 2025)
Historically, the most frequent cause of death reported to the Centers for Disease Control and Prevention (CDC) among travelers on conveyances has been cardiovascular disease, mirroring all-cause mortality in the US population. Infectious disease transmission, particularly during large-scale outbreaks, also poses a risk to travelers. To determine leading causes of death on conveyances and whether they were affected by the COVID-19 pandemic, we describe causes of death on conveyances reported to CDC from 2008 through 2022. We queried CDC's Port Health Activity Reporting System for traveler deaths on, or immediately after disembarking from, an aircraft or maritime vessel or during land-border crossings reported to CDC from July 1, 2008, through December 31, 2022. We examined data on cause of death, age, travel mode, and traveler type (passenger vs crew). We also calculated crude annual mortality rates for each conveyance type. To assess factors associated with deaths due to infectious diseases (vs deaths due to noninfectious conditions), we performed logistic regression. During the analysis period, 2910 deaths on conveyances were reported. Across all conveyances, the most common causes were cardiovascular- or pulmonary-related conditions (2116 of 2910; 73%) for each year except 2020, when COVID-19 was the most common. Crew (vs passengers) had significant associations with death due to infectious causes (vs noninfectious causes; adjusted odds ratio = 2.12; 95% CI, 1.32-3.40). Travelers with cardiovascular- or pulmonary-related conditions should consult their health care providers prior to international travel. All travelers should check travel recommendations such as those currently available on CDC travel pages. Public health authorities should consider population-based mitigation measures aimed at transmission risk reduction to limit morbidity and mortality during infectious disease outbreaks.